Association between exposure to per- and polyfluoroalkyl substances and kidney function: a population study - Zhang, Xue; Cao, Yongping; Yang, Xiaona; Ma, Fei; Zhang, Hengyang; Xiao, Wenwen (Frontiers in Medicine, 2025)
BackgroundThe relationship between per- and polyfluoroalkyl substances (PFAS) and kidney function markers remains uncertain.MethodsWe used PFAS detection data from 5,947 adults in NHANES 2005–2012. We employed multivariable linear regression models to examine associations between PFAS and estimated glomerular filtration rate (eGFR), urine creatinine (UCR), urine albumin (UAL), and urine albumin/creatinine ratio (UACR). To capture non-linear trends, restricted cubic splines were applied. The WQS (weighted quantile sum) and Q-gcomp (quantile g computation) models were used for the mixture analysis. Subgroup analyses were conducted to explore potential interactions.ResultsPerfluorooctanoic acid (PFOA), perfluorooctane sulfonic acid (PFOS), perfluorohexane sulfonic acid (PFHxS), 2-(N-methyl-perfluorooctane sulfonamido) acetic acid (N-MEFOSAA), and perfluorononanoic acid (PFNA) were negatively related to eGFR (β = −2.04, 95% CI = −2.85, −1.23; β = −0.97, 95% CI = −1.78, −0.16; β = −1.50, 95% CI = −2.24, −0.76; β = −0.49, 95% CI = −1.25, 0.27; β = −0.68, 95% CI = −1.46, 0.10). PFOA and PFOS were positive associated with UCR (β = 10.61, 95% CI = −1.89, 23.11; β = 12.98, 95% CI = 0.56, 25.41). PFOA, PFOS, PFHxS, PFNA, and PFUA were negatively related to UAL (β = −0.53, 95% CI = −0.73, −0.32; β = −0.39, 95% CI = −0.59, −0.18; β = −0.59, 95% CI = −0.78, −0.40; β = −0.42, 95% CI = −0.65, −0.19; β = −0.04, 95% CI = −0.22, 0.14). PFDA, PFOA, PFOS, PFHxS, and PFNA are significantly inversely associated with UACR (β = −0.01, 95% CI = −0.16, 0.14; β = −0.52, 95% CI = −0.69, −0.35; β = −0.50, 95% CI = −0.67, −0.33; β = −0.49, 95% CI = −0.64, −0.33; β = −0.27, 95% CI = −0.44, −0.10). Nonlinear relationships were found between PFAS and all kidney function indicators. Mixed PFAS exposure showed a negative association with eGFR, UAL and UACR, while showed a positive relationship with UCR. Interactions between PFASs and most subgroups were observed.ConclusionOur study revealed significant associations between PFAS exposure and various kidney function indicators. These findings provide an epidemiological perspective on how PFAS may lead to kidney dysfunction.